Impact of pheromone mating disruption and pesticides on oriental fruit moth (Grapholita molesta) on peaches - Lo, P.L.; Cole, L.M. (New Zealand Plant Protection, 2007)
Oriental fruit moth (OFM) is an important pest of summerfruit grown for both fresh market and processing in Hawkes Bay New Zealand Mating disruption was applied over three consecutive years on the same three cv Golden Queen peach orchards At each orchard plots of 0535 ha were treated with pheromone dispensers either alone or supplemented with insecticides In year one OFM populations were high and mating disruption or 12 insecticide applications did not provide sufficient control with up to 3 damage at harvest The following year all trial areas received pheromone dispensers plus one or two insecticide applications and fruit damage was at acceptable level of less than 1 In year three blocks with mating disruption alone averaged 02 OFM infestation compared with 09 where no OFM control was used OFM mating disruption is now increasingly being adopted by growers but the cost relative to insecticides is a barrier